ANALISIS PENDAPATAN RUMAH TANGGA MISKIN DI KABUPATEN TABANAN - Prayoga P, Kadek Bagus Reza; Yasa, I Gusti Wayan Murjana (E-Jurnal Ekonomi Pembangunan Universitas Udayana, 2025)
Poverty is a situation where there is an inability to fulfill basic needs such as clothing, food, education, shelter, also health. This research aims: 1) To analyze the simultaneous influence of the number of household dependents, working hours, employment status also education of the head of the household on the income of poor households in Tabanan Regency. 2) To analyze the influence of the number of household dependents, working hours, employment status and education of the head of the household partially on the income of poor households in Tabanan Regency. 3) To analyze the role of education of the head of the household in moderating the influence of employment status on the income of poor households in Tabanan Regency. keyword : Export; Consumption; Gross Domestic Product; Inflation; Exchange Rate